Demographic determinants of digital well-being among Indonesian library and information science students - Prabowo, Thoriq Tri; Sitthiworachart, Jirarat; Sriwisathiyakun, Kanyarat; Morris, John (My University, 2026)
This study examined the level of digital well-being among Indonesian library and information science students, focusing on demographic factors including gender, age, residency (urban vs rural), geographic location, and grade point average (GPA). Digital well-being is critical in effectively supporting learning in Library and Information Science. This study was a sequential explanatory design. Students from more than 15 universities over multiple regions participated in this self-assessment survey (n = 900). Quantitative data collected through an online survey based on Jisc’s digital well-being scale were analyzed using descriptive statistics, t-tests, and ANOVA. Qualitative data from follow-up surveys to selected students were thematically analyzed (n = 30). Positive impacts of digital well-being were higher than the negative ones. Gender, age, geographic location, and GPA affected digital well-being; but there was no difference between residency settings. Generally positive overall digital well-being beliefs were found among the students, with variations in some demographic factors. This study underscores the importance of digital well-being in a digital world. Valuable insights into the effective use of a two-stage survey demographics are provided, aiming to facilitate students in realizing the full potential benefits of digital technology use.
Keywords: Demographics; digital well-being; Indonesia; library and information science; self-assessment